2004
DOI: 10.1073/pnas.0307967101
|View full text |Cite
|
Sign up to set email alerts
|

Editing the stereochemical elements in an iridium catalyst for enantioselective allylic amination

Abstract: Individual diastereomeric phosphoramidites and mixtures of diastereomeric phosphoramidites were evaluated in the iridiumcatalyzed amination of allylic carbonates. The original process was conducted with a phosphoramidite ligand containing a resolved 2,2-dihydroxy-1,1-binaphthyl (BINOL) group and a diastereomerically and enantiomerically pure bis(phenethyl)amino group. Evaluation of the structure of the active catalyst and relative rates for reactions in the presence of catalysts containing diastereomeric ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Based on the structure of the active catalyst, Andreas Leitner developed sterochemically edited complexes that are nearly equivalent in activity and selectivity as the original system 52,53. The phenethyl substituent attached the metallacyclic core of the structures in Scheme 2 and Figure 2 is distal from the metal center, and, we proposed that this substituent could be replaced by a group lacking any stereocenter (Figure 3).…”
Section: Studies On Catalysts Having Edited Stereochemistrymentioning
confidence: 99%
“…Based on the structure of the active catalyst, Andreas Leitner developed sterochemically edited complexes that are nearly equivalent in activity and selectivity as the original system 52,53. The phenethyl substituent attached the metallacyclic core of the structures in Scheme 2 and Figure 2 is distal from the metal center, and, we proposed that this substituent could be replaced by a group lacking any stereocenter (Figure 3).…”
Section: Studies On Catalysts Having Edited Stereochemistrymentioning
confidence: 99%
“…Encouraged with this result, we extended this strategy to prepare bis-naphthyl phosphoramidite 5 (Scheme 2). This catalyst was found to be useful for iridium catalyzed amination of allylic carbonates (Leitner et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Iridium-catalyzed allylic amination has emerged as an important method for enantioselective C À N bond formation. [1][2][3][4][5][6][7][8][9] Pursuant to the pioneering work of Takeuchi, [1,2] studies from the laboratories of Helmchen, [3,4] Hartwig, [5,6] Carreira, [7] and You [8,9] have shown that chiral phosphoramidite-modified iridium complexes are especially effective in this regard (Figure 1). Like the parent palladium-catalyzed Tsuji-Trost reactions, [10] the iridium-phosphoramidite-catalyzed allylic alkylations occur via cationic p-allylmetal intermediates.Recently,wefound that p-allyliridium-C,O-benzoates,w hich are wellknown to promote nucleophilic allylation of carbonyl compounds, [11,12] are also effective catalysts for highly regio-and enantioselective electrophilic allylation of amines.…”
mentioning
confidence: 99%